Effect of Eased Restrictions for ACA-Exempt Short-Term Health Plans on Marketplace Premiums and Uninsured Rate: A Difference in Differences Analysis - Sergei S. Kostiaev PhD; Sujoy Chakravarty PhD; Joel C. Cantor ScD (SAGE Publishing, 2023)
The Affordable Care Act (ACA) established broad standards for private health insurance in the United States including requiring minimum essential benefits and prohibiting medical underwriting, but the law also permitted some exceptions. This paper examines one type of exempt plan option, Short-Term, Limited Duration Insurance (STLDI) that is not required to fully meet ACA benefit and underwriting standards. Federal rules governing STLDI plans have changed over time, with more permissive rules in the Trump administration allowing individuals to remain covered for longer durations of time relative to the original Obama regulations. Within applicable federal guidelines, states have also varied STLDI rules. Using publicly available data measuring state-level variations in STLDI regulations, ACA benchmark premiums, uninsured rates, and population characteristics for 2014 to 2021, we estimate difference-in-differences models to examine if more permissible STLDI policies are associated with higher premiums in the fully regulated non-group market and, also, lower uninsured rates. We find that longer duration, more permissible STLDI is associated with higher benchmark premiums in ACA exchanges and no difference in state-level uninsured rates. Trump administration regulations permitting longer duration STLDI plans to make available more affordable ACA-exempt health insurance were associated with higher premium costs in the ACA-regulated non-group market but we did not observe measurable impact on state uninsured rates. While longer-duration STLDI plans may result in lower costs for some, they have negative consequences for others requiring comprehensive coverage with no discernible benefit in overall coverage rates. Understanding these tradeoffs can help guide future policies regarding exceptions to ACA plan requirements.